La evaluación por calidad del gasto y su incidencia en la adecuada ejecución presupuestaria en la Dirección Regional de Salud - Cajamarca, Período 2014. - Luna De Los Rios, Antony (2016)
Today the public sector institutions dependent health of a budget statement to make use of state resources in the implementation of projects for continuous improvement of the Peruvian state, the institution implements the budget in compliance with the budgetary targets reporting monthly to the office in charge of planning and budget of the institution, so the end of the prepuestario cycle performs an assessment that generally measure the amount executed in relation to the budget, evaluating and if all public expenditure was implemented in compliance with the budget, so this evaluation by the institution may have some limitations that were addressed in this study, to measure control the expenses of the institution in the implementation of its budget to show whether the expenses used by the institution are conducted in compliance with health standards current, thus reflecting the efficiency of public resources and good management of health administration to implement the budget with expenditures of quality that contribute to the welfare of Peruvians. So this paper contains a study on budget execution controlled by evaluating the quality of spending, for it has audited the budget year 2014, leaning on the area information budget the results of the budget execution were measured, causality that own their acquisitions and whether they are associated with a program with a goal, finally the results were compared with the result of the budget execution indicators, the relationship between the indicators presented by the entity and control use evidence the resources of the entity by spending quality; evaluation by spending quality has its reason for being in the relationship that has a public spending with the goals that the body is drawn, in this sense the budget statement reflects this theory and implements specific programs which presupposed any acquisition that believes suitable to achieve the specific objective of the program, these acquisitions by nature should be classified as an expense of quality be related directly to a target, so in the evaluation of budget execution recognizes whether this acquisition has logic within your program, as when compared with the other group of spending that does not have a program with certain specific objectives or are out of a budget program, the result of this comparison is the efficiency of each expenditure group resultsoriented budget execution of the public body.